The Role of River Flooding as an Environmental Filter for Amazonian Butterfly Assemblages - Rabelo, Rafael M.; Pereira, Geanne C. N.; Valsecchi, João; Magnusson, William E. (Frontiers in Ecology and Evolution, 2021)
Amazonian flooded (várzea) and upland (terra firme) forests harbour distinct assemblages of most taxonomic groups. These differences are mainly attributed to flooding, which may affect directly or indirectly the persistence of species. Here, we compare the abundance, richness and composition of butterfly assemblages in várzea and terra firme forests, and evaluate whether environmental gradients between and within these forest types can be used to predict patterns of assemblage structure. We found that both total abundance and number of species per plot are higher in várzea than in terra firme forests. Várzea assemblages had a higher dominance of abundant species than terra firme assemblages, in which butterfly abundances were more equitable. Rarefied species richness for várzea and terra firme forests was similar. There was a strong turnover in species composition from várzea to terra firme forests associated with environmental change between these forest types, but with little evidence for an effect of the environmental gradients within forest types. Despite a smaller total area in the Amazon basin, less defined vegetation strata and the shorter existence over geological time of floodplain forests, Nymphalid-butterfly assemblages were not more species-poor in várzea forests than in unflooded forests. We highlight the role of flooding as a primary environmental filter in Amazonian floodplain forests, which strongly determines the composition of butterfly assemblages.